Processi cognitivi e apprendimento della chimica: uno studio pilota sulla popolazione universitaria a sviluppo tipico - De Vita, Francesca; Ghibaudi, Elena; Lombardo, Renato; Maggio, Antonella Maria; Re, Anna Maria; Sini, Barbara (Chimica nella Scuola, 2024)
The national surveys have observed that Italian students perform significantly worst in the science field compared to their international peers. This is also true when we consider a particular subject, such as chemistry. This is partially explained by teaching practice since the Italian school context rarely allows the possibility to organise and implement interactive teaching strategies. Consequently, most of students learn chemistry by memorizing definitions without reaching a full understanding. Moreover, professors do not have the opportunity to acquire knowledge about the cognitive processes involved in chemistry learning and the teaching strategies that might be used to overcome the conceptual difficulties of the discipline. In addition, they are not aware of the peculiar difficulties of students with Specific Learning Disorder (SLD) and the compensatory measures that could be carried out to improve their learning performance in the science field. Therefore, the present project has the main goal of extending the knowledge on cognitive processes involved in chemistry learning of undergraduates’ students, to design effective strategies and compensative measure that will improve students’ chemistry learning ability. The present paper reports the results of a pilot investigation, which tested the adequacy of a chemistry learning test on a small sample of Italian undergraduate students.